Social Identity Approach and Historical Research on the Early Modern Era - Mikkola, Sini (Approaching religion, 2026)
This review article explores the applicability of the Social Identity Approach (SIA) in historical research, focusing on research and sources from the Early Modern era, particularly the context of the Lutheran Reformation. The study argues that while identity is often treated as self-evident in religious historical research, SIA offers conceptual tools that can enrich historical interpretation. Using examples from sixteenth- and seventeenth-century writers’ texts, the article demonstrates how boundaries of "true Christianity" were negotiated and maintained, and how the conceptualizations of SIA could be used in these discussions. It also highlights methodological challenges: historians lack direct access to human cognitive processes and must rely on mediated, fragmentary sources, which necessitates contextualization and source criticism to avoid anachronism. SIA should therefore be employed as a heuristic framework rather than a predictive model. When applied critically, it enables nuanced analysis of identity construction and group dynamics, fostering interdisciplinary dialogue between history and social psychology.